Male and female inheritance patterns in tetraploid ‘Moncada’ mandarin - Garavello, Miguel Fernando (2019)
Triploid-breeding programs in citrus are key tool to develop seedless cultivars. Obtaining triploid citrus hybrids may be achieved through different strategies, such as the exploitation of female unreduced gamete in crosses between diploid parents and diploid by tetraploid sexual hybridizations, in which tetraploid genotypes can be used as male or female parents. Genetic configuration of triploid populations from interploid crosses greatly depends on the chromosomic segregation mode of the tetraploid parent used. Here, we have analyzed the inheritance of the tetraploid ‘Moncada’ mandarin and compared the genetic structures of the resulting gametes when used as male and as female parent. The preferential chromosome pairing rate is calculated from the parental heterozygosity restitution (PHR) of codominant molecular markers, indicating the proportion between disomic and tetrasomic segregation. Tetraploid ‘Moncada’ both as female and male parent largely exhibited tetrasomic segregation. However, as female parent, one linkage group (LG8) showed intermediate segregation with tendency towards tetrasomic inheritance, while another linkage group (LG4) evidenced a clear intermediate segregation. On the other hand, when used as male parent two linkage groups (LG5 and LG6) showed values that fit an intermediate inheritance model with tetrasomic tendency. Significant doubled reduction (DR) rates were observed in five linkage groups as female parent, and in six linkage groups as male parent. The new knowledge generated here will serve to define crossing strategies in citrus improvement programs to efficiently obtain new varieties of interest in the global fresh consumption market.